Liability of the prospectus a comparison between South Africa and Germany - Zschiesche, Jan Hendrik (Department of Commercial Law, 2026)
A levelled basis of information for all market participants, market transparency as well as the integrity of the market are indispensable prerequisites for the_protection of financial investors: However, any legislative protection of investors does not aim to reduce the typical investment risks of risk papers but rather to lower risks which exceed those typical risks.